Escaping Immoral Plants: the Dynamic of Access and the Moral Economy of Tobacco Farming on the Slopes of Sindoro-Sumbing - Priharwanto, Novi (UI Scholars Hub, 2024)
In recent years, tobacco farmers on the slopes of Mount Sindoro and Sumbing (Sinsu), Central Java, have experienced a downturn due to the increasingly falling price of dry chopped tobacco. Instead of making a profit, they are in debt to middlemen, which they may not be able to pay off until the next planting season. As a result, many of the farmers decided to switch to agricultural cultivation or quit tobacco altogether. This research argues that the process of the farmers’ leaving tobacco is also influenced by the dynamics of access and the moral economy, as manifest in the metaphor of the